PENERAPAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA PENCURIAN SEPEDA MOTOR DI WILAYAH HUKUM POLSEK KUTA UTARA - I Wayan Eka Artajaya (Jurnal Ilmiah Raad Kertha, 2026)
Restorative justice, as a means of peacefully resolving conflicts outside the courts, remains difficult to implement. In Indonesia, many customary laws can be used as restorative justice, but their existence is not recognized by the state or codified in national law. Customary law can resolve conflicts that arise in society and provide satisfaction to the conflicting parties. The idea of restorative justice emerged as a critique of the criminal justice system, which relies on imprisonment for resolving social conflict, which is considered ineffective. This is because the parties involved in the conflict are not involved in conflict resolution. Victims remain victims, and perpetrators are imprisoned, creating new problems for families, and so on.